PELINDUNGAN SOSIAL BAGI LANSIA: STUDI TENTANG PENGALAMAN LANSIA YANG TERABAIKAN DI YAYASAN BERINGIN BHAKTI DI CIREBON - Faqih, Ahmad Jauharul; Musahwi (Yayasan Amanah Nur Aman, 2025)
The increasing number of elderly people in Indonesia encourages the importance of a comprehensive social protection system, especially for neglected elderly groups who are physically, socially and psychologically vulnerable. This study aims to examine in depth the experience of neglected elderly people in receiving social protection at Beringin Bhakti Foundation, Cirebon Regency. The method used is descriptive qualitative research with data collection techniques in the form of semi-structured interviews, observation, and documentation of four elderly informants and one caregiver. The results showed that the social protection provided included fulfillment of basic needs, health services, spiritual guidance, skills empowerment, and integrated psychosocial assistance. This intervention has proven to be able to restore the physical and emotional condition of the elderly, build a sense of security, and restore their dignity as valuable individuals. Support from the Social Service, volunteers and the community are the main supporting factors, although there are still obstacles in the form of lack of family involvement. This research contributes to the development of an elderly social protection model based on a holistic and community approach.